The Concepts of Economic Resilience: An Information and Technology Based Assesment (Case Study of Micro and Small Enterprises in Jakarta) - Dedi Purwana; M.Yasser Arafat Marsellisa Nindito; Diena Noviarini (Jurnal Ilmiah Wahana Akuntansi, 2013)
ABSTRACT This researchaimed to find out what explains the concepts of economic resilience through information and technology based assesment for the purpose of studying the micro and small enterprises in The Jakarta Province. In collecting the research datas, interviews were being conducted while the answers from the informants would lead the researchers’ conclusions. Thisresearch have resulted on confirmation that there is a growing trend of economic development in the community of micro and small industrial center as a way to enhance economic resilience. The Jakarta province should reinforce this kind and a like industrial center to build the strengths of the enterprises as economic stimulation to the community. Another result is in the terms of information and technology based assesment, we have found that the concepts of economic resilience could be achieved through the distribution of economic development in the attempt of increasing businesses’ productivity as the result of information and technology applications. Furthermore,the respectively regulation and laws coming from the authorities have provided the protection and guidence needed by the enterprises in the creation of economic development and long-term businesses’ growth. Keywords: stimulation, economic development, long-term businesses growth, information and technology based assesment